The influence of consumer perception of brand on purchase decisions at Mie Gendowor Pringsewu - Annisa Fitria; Wagiyo Wagiyo; Juliono Juliono; Arohman Arohman (Enrichment : Journal of Management, 2023)
Purchasing decisions are consumer actions whether they want to buy products or not, whether there is an influence on consumer perceptions on purchasing decisions, because everyone has a different object, perception has a subjective nature, brand is a reflection of the associations that exist in consumer minds, is there any influence on decisions purchases, whether brand and consumer perceptions influence simultaneously on purchasing decisions at Mie Gendowor Pringsewu. This type of research uses quantitative methods, the data collection uses documentation and questionnaires, with the customer population; the sample was calculated using the Cochran Formula to produce 96 samples, but the questionnaires returned by customers were 88. Data analysis used multiple linear regression with hypothesis testing using t-test and f-test. Conclusions in this study; There is an influence of consumer perceptions on purchasing decisions which is indicated by the presence